Why Do They Have to Flaunt it? Perceptions of Communicative Intent Predict Antigay Prejudice Based Upon Brief Exposure to Nonverbal Cues. (November 2014) - Lick, David J.; Johnson, Kerri L.; Gill, Simone V.
Perceivers use gender-atypical nonverbal cues to categorize others as lesbian/gay, and the same cues help to explain the occurrence of antigay prejudice. Although these patterns replicate across recent studies, their proximal causes have received little attention. It remains unclear, for example, why the gender-atypical appearances common among sexual minority individuals arouse negative evaluations. Here, we tested whether perceptions of communicative intent—believing that targets' visible features are deliberately enacted in order to convey aspects of their identities—may help to explain observed links between sexual orientation categorization, gender typicality, and prejudice. In Study 1, gender-atypical body motions were associated with the perception that targets were intentionally trying to communicate their identity, and perceptions of communicative intent predicted expressions of antigay prejudice. Study 2 replicated these effects with static facial images. Collectively, these findings highlight communicative intent as an important factor predicting antigay prejudice in the early moments of social perception.